Chinese immigrants and their descendants, a look inside their life stories - Chen Mok, Susan (2018)
The objetive of this research paper is to recover the life stories of Chinese immigrants and / or their descendants of Puntarenas city in the 20th century to contribute to the construction of the process of Chinese immigration in Costa Rica. This study analizes of the life stories of eighteen immigrants and / or direct descendants of these, all of them senior citizens in the 20th century. The life story technique proposed by Bertaux (2005) is used. The conclusions show that the Chinese community has inserted itself into the community of Puntarenas in a peaceful and friendly way, contributing its cultural features and customs and integrating itself into the daily life of this city.